Determination of the Size and Depth of Craters on the Moon - Vladimir Grubelnik; Marko Marhl; Robert Repnik (Center for Educational Policy Studies Journal)
Experimental work in the research of astronomical phenomena is often difficult or even impossible because of long-lasting processes or too distant objects and correspondingly too expensive equipment. In this paper, we present an example of observation of the Moon, which is our nearest astronomic object and therefore does not require professional astronomic equipment for observation. We focus on the observation of craters on the Moon, determining their lateral size and depth on the basis of photographs and simple calculations. The fieldwork with students of junior grade school education was performed within the framework of the optional subject Astronomy. An analysis of the results of the students’ experimental work, as well as of curricula on various levels of education, led us to conclusion that this kind of experimental work is suitable for incorporation in secondary school physics education. With some mathematical simplifications, however, the treatment of the topic can also be appropriate in primary school. Such experimental work enables students to gain specific natural science and mathematical competences that are also required for the study of other natural  phenomena.